Design and Optimization of a High Gain Multiband Patch Antenna for Millimeter Wave Application - A. Zaidi; A. Baghdad; A. Ballouk; A. Badri (Institute of Advanced Engineering and Science, 2018)
This paper presents an enhanced Quadri-band microstrip patch antenna, using defective slots in the ground plane, designed to operate in the millimeter wave band, formulated using cavity model and simulated by an EM-simulator, based on finite element method: HFSSv15 (High Frequency Structure Simulator). The proposed antenna incorporates two symmetric patterns of “U” shaped slots with an “I” shaped slot engraved in the middle of the ground plane. The resulting antenna has four frequency bands; the first resonant frequency is located in the Ka band, at about 27Ghz, the second at nearly 35Ghz, the third at 41Ghz and the last one at 51GHz. Those resonant frequencies could be shifted by tuning the slots dimensions introduced if the ground plane of the proposed antenna .